NPD-0414-2 and NPD-0414-24, Two Chemical Entities Designed as Aryl Hydrocarbon Receptor (AhR) Ligands, Inhibit Gut Inflammatory Signals - Marafini, Irene; Di Fusco, Davide; Dinallo, Vincenzo; Franzè, Eleonora; Stolfi, Carmine; Sica, Giuseppe; Monteleone, Giovanni; Monteleone, Ivan (Frontiers in Pharmacology, 2019)
Defects in counter-regulatory mechanisms contribute to amplify the detrimental inflammatory response leading to the pathologic process occurring in the gut of patients with Crohn’s disease (CD) and ulcerative colitis (UC), the major inflammatory bowel diseases (IBD) in human beings. One such a mechanism involves Aryl hydrocarbon Receptor (AhR), a transcription factor activated by natural and synthetic ligands, which induces the production of interleukin (IL)-22 and down-regulates inflammatory signals. In IBD, AhR expression is down-regulated and its activation by natural ligands promotes clinical and endoscopic benefit. Since the use of AhR natural ligands can associate with serious adverse events, we developed new chemical ligands of AhR and assessed their regulatory effects. Among these derivatives, we selected the compounds NPD-0414-2 and NPD-0414-24, as they displayed the more pronounced capacity to induce IL-22. Peripheral blood mononuclear cells and lamina propria mononuclear cells (LPMC) were isolated from CD and UC patients. Cells were treated in vitro with Ficz, AhR ligands and AhR antagonist and then cytokines’ expression was evaluated by real-time PCR and flow cytometry. After the induction of TNBS colitis, Ficz and AhR ligands were injected intra-peritoneally to wild-type and AhR knock-out mice. After 4 days mice were sacrificed and colonic tissues were collected for histologic examination and real-time PCR analysis. Treatment of IBD LPMC with NPD-0414-2 and NPD-0414-24 reduced IFN-γ and increased IL-22 transcripts, and these effects were abrogated by CH223191, a specific inhibitor of AhR interaction with its ligands. Mice given NPD-0414-2 and NPD-0414-24 developed a significantly less severe form of TNBS colitis and exhibited reduced expression of IFN-γ and increased expression of IL-22. The therapeutic effect of NPD-0414-2 and NPD-0414-24 on the ongoing colitis was abrogated in AhR-deficient mice. Collectively, these data show that NPD-0414-2 and NPD-0414-24 exert Ahr-dependent regulatory effects in the gut.